Pengaruh Bermain Peran Terhadap Peningkatan Kemampuan Sosial Anak Usia Dini - Choirun Nisak Aulina (Universitas Trunojoyo Madura, 2014)
Many parents, teachers and the public assume that kindergarten is the only institution to prepare children entering elementary school. Thus, the learning process is limited to the development of the ability to read, write, and count, so the chance of improving social skills neglected. Social skills in children needs to be extracted and grown by improving materials and teaching methods provided by the teacher. Playing the role of a learning method that provides opportunities for children to develop imagination, as well as practicing socialize, communicate and empathize with other children. Research aims: 1). To know the difference between a child social skill play a role given treatment and children who were not given the treatment play a role; 2). To know how to play the role and influence of not playing the role of the social skills of children. Quantitative approach to the type of quasi-experimental study (quasi). The research sample of 40children TK B Aisyiyah 6 Tanggulangin. Results showed treatment play a role and given treatment without playing the role Mann-Whitey U Value of 1000 and Wilcoxon W value of 211,00, significance value of 0,000. Because the probability value is much smaller than the significance level of 0,05 or (0,000 0,05), then the experimental group with treatment play a role much better than the untreated control group plays the role of the social skills of early childhood.